Longitudinal Evaluation of Sympathetic Nervous System and Perfusion in Normal and Spontaneously Hypertensive Rat Hearts with Dynamic Single-Photon Emission Computed Tomography. Issue 7 (1st July 2015) - Zan, Yunlong; Boutchko, Rostyslav; Huang, Qiu; Li, Biao; Chen, Kewei; Gullberg, Grant T.
The objective of this work was to evaluate the sympathetic nervous system and structure remodeling during the progression of heart failure in a rodent model using dynamic cardiac single-photon emission computed tomography (SPECT). The spontaneously hypertensive rat (SHR) model was used to study changes in the nervous system innervation and perfusion in the left ventricular (LV) myocardium with the progression of left ventricular hypertrophy (LVH) to heart failure. Longitudinal dynamic SPECT studies were performed with seven SHR and seven Wistar-Kyoto (WKY) rats over 1.5 years using a dual-head SPECT scanner with pinhole collimators. Time-activity curves (TACs) of the 123 I-MIBG and 201 Tl distribution in the LV blood pool and myocardium were extracted from dynamic SPECT data and fitted to compartment models to determine the influx rate, washout rate, and distribution volume (DV) of 123 I-MIBG and 201 Tl in the LV myocardium. The standardized uptake values (SUVs) of 123 I-MIBG and 201 Tl in the LV myocardium were also calculated from the static reconstructed images. The influx and washout rates of 123 I-MIBG did not show a significant difference between SHRs and WKY rats. The DVs of 123 I-MIBG were greater in the SHRs than in the WKY rats ( p = .0028). Specifically, the DV of 123 I-MIBG became greater in the SHRs by 6 months of age ( p = .0017) and was still significant at the age of 22 months. The SUV of 123 I-MIBG in SHRs exhibited abnormal values compared to WKY rats from the age of 18 months. There was no difference in the influx rate and the washout rate of 201 Tl between the SHRs and WKY rats. The SHRs exhibited greater DV of 201 Tl than WKY rats after the age of 18 months ( p = .034). The SUV of 201 Tl in SHRs did not show any significant difference from WKY at all ages. The higher DV of 123 I-MIBG in the LV myocardium reveals abnormal nervous system activity of the SHRs at an age of 6 months, whereas a greater DV of 201 Tl in the LV myocardium can only be detected at an age of 18 months. The results show that the abnormal nervous system activity appears earlier than perfusion. Furthermore, the comparison between the DV and the SUV indicates that dynamic SPECT with 123 I-MIBG and 201 Tl with the kinetic parameter DV is capable of detecting abnormalities of the LV at an early age.